Dimerization effects on coacervation property of an elastin‐derived synthetic peptide (FPGVG)5. (April 2016) - Suyama, Keitaro; Taniguchi, Suguru; Tatsubo, Daiki; Maeda, Iori; Nose, Takeru
Abstract : Elastin, a core protein of the elastic fibers, exhibits the coacervation (temperature‐dependent reversible association/dissociation) under physiological conditions. Because of this characteristic, elastin and elastin‐derived peptides have been considered to be useful as base materials for developing various biomedical products, skin substitutes, synthetic vascular grafts, and drug delivery systems. Although elastin‐derived polypeptide (Val‐Pro‐Gly‐Val‐Gly) n also has been known to demonstrate coacervation property, a sufficiently high (VPGVG) n repetition number ( n > 40) is required for coacervation. In the present study, a series of elastin‐derived peptide (Phe‐Pro‐Gly‐Val‐Gly)5 dimers possessing high coacervation potential were newly developed. These novel dimeric peptides exhibited coacervation at significantly lower concentrations and temperatures than the commonly used elastin‐derived peptide analogs; this result suggests that the coacervation ability of the peptides is enhanced by dimerization. Circular dichroism (CD) measurements indicate that the dimers undergo similar temperature‐dependent and reversible conformational changes when coacervation occurs. The molecular dynamics calculation results reveal that the sheet‐turn‐sheet motif involving a type II β‐turn‐like structure commonly observed among the dimers and caused formation of globular conformation of them. These synthesized peptide dimers may be useful not only as model peptides for structural analysis of elastin and elastin‐derived peptides, but also as base materials for developing various temperature‐sensitive biomedical and industrial products. Copyright © 2016 European Peptide Society and John Wiley & Sons, Ltd. Abstract : A series of elastin‐derived peptide (Phe‐Pro‐Gly‐Val‐Gly)5 dimers possessing high coacervation potential were synthesized. The new dimeric peptides showed significantly high coacervation ability compared to known elastin‐derived peptide analogs. The molecular dynamics calculation results reveal that the dimeric peptides contain characteristic sheet‐turn‐sheet motif involving a type II β‐turn‐like structure and form globular conformation.